Analysis Of Anxiety Levels Of Pregnant Women During The Covid-19 Pandemic In Indonesia - Sabrin, Gusriani; Retnowati, Yuni; Noviyanti, Nur Indah; Sunardi, Wahida; Sutrang, Darmiati (Publisher Cv. Inara, 2021)
Coronavirus Disease 2019 (Covid-19) is a new type of disease caused by the Sars-CoV-2 virus. The unpredictability of the Covid-19 pandemic makes people prone to severe anxiety. Anxiety is a normal reaction to uncertainty and things that may harm. Research has shown that pregnant women are especially prone to anxiety with the prevalence of gestational anxiety. The impact of the COVID–19 pandemic on pregnancy-related anxiety has yet to be systematically studied. This research aims to assess the level of anxiety of pregnant women during the Covid-19 pandemic and to analyze the causes. This type of research is descriptive-analytic with the cross-sectional approach. The study was conducted in March-April 2020 with a total of 154 pregnant women respondents from various regions in Indonesia. The results showed that the majority of respondents were not anxious, namely 89 respondents (57.8%), respondents with mild anxiety were 58 respondents (37.7%), moderate anxiety was 5 respondents (3.2%) and severe anxiety was 2 respondents (1.3%). The low rate of anxiety in pregnant women during the Covid-19 pandemic was due to the availability of information about the causes, modes of transmission, and massive prevention of Covid-19 through various media as well as guaranteed services and availability of health facilities.